Genetics and genotype–phenotype correlations in early onset epileptic encephalopathy with burst suppression. Issue 3 (14th February 2017) - Olson, Heather E.; Kelly, McKenna; LaCoursiere, Christopher M.; Pinsky, Rebecca; Tambunan, Dimira; Shain, Catherine; Ramgopal, Sriram; Takeoka, Masanori; Libenson, Mark H.; Julich, Kristina; Loddenkemper, Tobias; Marsh, Eric D.; et al.
Abstract : Objective: We sought to identify genetic causes of early onset epileptic encephalopathies with burst suppression (Ohtahara syndrome and early myoclonic encephalopathy) and evaluate genotype–phenotype correlations. Methods: We enrolled 33 patients with a referral diagnosis of Ohtahara syndrome or early myoclonic encephalopathy without malformations of cortical development. We performed detailed phenotypic assessment including seizure presentation, electroencephalography, and magnetic resonance imaging. We confirmed burst suppression in 28 of 33 patients. Research‐based exome sequencing was performed for patients without a previously identified molecular diagnosis from clinical evaluation or a research‐based epilepsy gene panel. Results: In 17 of 28 (61%) patients with confirmed early burst suppression, we identified variants predicted to be pathogenic in KCNQ2 (n = 10), STXBP1 (n = 2), SCN2A (n = 2), PNPO (n = 1), PIGA (n = 1), and SEPSECS (n = 1). In 3 of 5 (60%) patients without confirmed early burst suppression, we identified variants predicted to be pathogenic in STXBP1 (n = 2) and SCN2A (n = 1). The patient with the homozygous PNPO variant had a low cerebrospinal fluid pyridoxal‐5‐phosphate level. Otherwise, no early laboratory or clinical features distinguished the cases associated with pathogenic variants in specific genes from each other or from those with no prior genetic cause identified. Interpretation: We characterize the genetic landscape of epileptic encephalopathy with burst suppression, without brain malformations, and demonstrate feasibility of genetic diagnosis with clinically available testing in >60% of our cohort, with KCNQ2 implicated in one‐third. This electroclinical syndrome is associated with pathogenic variation in SEPSECS . Ann Neurol 2017;81:419–429